A New Benchmark Capacitance for Supercapacitor Anodes by Mixed‐Valence Sulfur‐Doped V6O13−x. (30th July 2014) - Zhai, Teng; Lu, Xihong; Ling, Yichuan; Yu, Minghao; Wang, Gongming; Liu, Tianyu; Liang, Chaolun; Tong, Yexiang; Li, Yat
<x xml:space="preserve">Abstract</x> A new pseudocapacitor anode, sulfur‐doped V6O13−x, is reported. It achieves a benchmark capacitance of 1353 F/g (0.72 F/cm2) at a current density of 1.9 A/g (1 mA/cm2) in 5 M LiCl solution. The charges are stored chemically in the electrode via reversible redox reactions that involve multiple oxidation states of vanadium (V3+, V4+ and V5+). <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>